The effect of brotowali (Tinospora crispa L.) stem ethanolic extract on the inhibition of Candida albicans biofilm formation - Suryani Hutomo; Christiane Marlene Sooai; Maria Silvia Merry; Ceny Gloria Larope; Haryo Dimasto Kristiyanto (Dental Journal (Majalah Kedokteran Gigi), 2022)
Background: Candida albicans (C. albicans) is an opportunistic pathogen that can be found in the oral cavity and other parts of the body. This species is the main cause of oral candidiasis and forms a biofilm as its virulence factor. Due to increasing cases of antifungal resistance, research is needed on methods to control Candida biofilm formation. Brotowali (Tinospora crispa L.) is known to be antifungal, antiseptic and antiparasitic. Purpose: The purpose of this study is to analyse the ability of brotowali stem extract to inhibit Candida biofilm formation. Methods: The susceptibility of C. albicans to this extract was examined by a minimum inhibitory concentration (MIC) test using the broth microdilution method. A bacterial adherence assay was performed by similar methods of the MIC assay. A brotowali stem extract of various concentrations were incubated in a yeast peptone dextrose broth medium and stimulated with a C. albicans suspension. The 0.1% crystal violet was used to stain the adherent fungi and measured using a microplate reader at 595 nm. Scanning electron microscopy (SEM) was performed to provide a general overview of the biofilm formation. Results: The MIC value for the brotowali stem extract was at a concentration of 5,000 μg/ml. Moreover, this extract inhibited fungal adherence starting at a concentration of 250 μg/ml. Observation using SEM confirmed these results. Statistical analysis using one-way analysis of variance demonstrated a significant difference of C. albicans adherence following stimulation with brotowali extract (p < 0.005). Conclusion: Brotowali stem extract can inhibit C. albicans biofilm formation at an optimal concentration of 1,000 μg/ml.